INVESTIGATION OF HYDRAULIC OPERATIONAL REGIMES OF CIRCULATING SYSTEM AT THERMAL POWER PLANT OF VOLZHSKY AUTOMOTIVE WORKS USING COMPUTER MODEL - V. V. Dikop; A. V. Bukhtiarov; A. G. Kovalenko; V. V. Kotov; V. A. Kudinov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Investigation results of hydraulic operational regimes of a circulating system with the help of a computer model are presented in the paper. The models simulates hydraulic processes by means of an iterated solution of a set of algebraic non-linear equations that is formed while using a graph theory The circulating system is considered as a unit in the model. The model program makes it possible to calculate consumption and pressure at any point of the circulating system with indication of flow motion directions along its separate branches and also to execute some economical calculations.